Modern Thailand - Slagter, Robert. (McGraw-Hill, 2000)
Modern Thailand. A brief history of Thauland. The Thai economy, economic development, and the modern world system. The Thai political system. Social stratification in Thailand. Religion in Thailand. The family and education in Thailand. Social change and social problems in modern Thailand.